(untitled) (Physical Culture and Sport: Scientific Perspective, 2025)
The article assesses the daily routine in the organization of children’s recreation and health improvement, which is characterized by the lack of strict regulation of their life activities. Observations were made of children aged 11-12 years (14 boys and 17 girls) during a summer health camp that lasted from July 2 to 22, 2024. The study of the daily routine was conducted using a questionnaire. Its impact on the functional state of children was assessed by indicators of the dynamics of the functional state of the cardiovascular, respiratory and nervous systems. It was found that in the conditions of free choice of leisure, children choose their favorite lifestyle. Children who have been involved in physical education and sports during the school year prefer active leisure. One of the favorite types of physical activity for children was walking to Ukrainian songs, and outdoor games were also popular. The results of the survey showed that almost a quarter of children (25.2%) did not attend any physical education classes during the shift. Given the free choice of leisure activities, children in the camp prefer the activities they are used to. In this regard, the organizers were recommended to engage more actively in physical activities those who usually choose passive recreation. Thus, in conditions of free choice of leisure activities, children in the camp prefer the activities that are familiar to them. It is shown that children with a high level of motor activity had more favorable dynamics of the functional state of the body during their stay in the camp than their peers who preferred passive recreation, and vice versa. A comparative analysis of the dynamics of indicators of the functional state of the body of children with different levels of physical activity (PA) showed that children with a high level of PA have better initial indicators and positive dynamics. Violations of the main regimen moments, such as the duration of sleep and the frequency of meals, were revealed. Therefore, the organization of a rational regimen requires enhanced monitoring of children’s compliance with the main regimen points.